The Role of Accounting Information Systems In Management Decision Making at PT. Kawi Heritage Raharja (Wings) Bantaeng District - Ramli, Muh.; Dangkeng, Arianto; Fausiah, Rafika; Hasrul Wijaya, Hasrul Wijaya (INVOICE : JURNAL ILMU AKUNTANSI, 2024)
This research aims to determine the role of accounting information systems in management decision making at PT. Kawi Pusaka Raharja (Wings) Bantaeng Regency. This research is a type of research that is descriptive qualitative in nature. Data collection was carried out by means of observation, interviews and documentation. The data analysis methods used are data reduction, data presentation, and drawing conclusions/verification. Based on the results of the research that has been carried out, it can be concluded that the accounting information system at PT. Kawi Pusaka Raharja (Wings) Bantaeng Regency plays an important role in management decision making, because the computerized accounting information system and the quality of the accounting information system used is very effective and efficient so that management, especially managers in the company, make it easier to make decisions. Accounting information systems have played a very important role in decision making at PT. Kawi Pusaka Raharja (Wings) Bantaeng Regency despite the problems experienced in the accounting information system process, where often all activities and transactions within the company become hampered due to poor networking. However, this does not reduce the function of the accounting information system in decision making